Resting State fMRI Networks in Children with Tuberous Sclerosis Complex - Ahtam, Banu (J Neuroimaging, 2019)
BACKGROUND AND PURPOSE: There are no published studies examining resting state networks (RSNs) and their relationship with neurodevelopmental metrics in tuberous sclerosis complex (TSC). We aimed to identify major resting-state functional magnetic resonance imaging (rs-fMRI) networks in infants with TSC and correlate network analyses with neurodevelopmental assessments, autism diagnosis, and seizure history. METHODS: Rs-fMRI data from 34 infants with TSC, sedated with propofol during the scan, were analyzed to identify auditory, motor, and visual RSNs. We examined the correlations between auditory, motor, and visual RSNs at ~11.5 months, neurodevelopmental outcome at ~18.5 months, and diagnosis of autism spectrum disorders at ~36 months of age. RESULTS: RSNs were obtained in 76.5% (26/34) of infants. We observed significant negative correlations between auditory RSN and auditory comprehension test scores (p=0.038; r=−0.435) as well as significant positive correlations between motor RSN and gross (p=0.023; r=0.564) motor skills test scores. Significant positive correlations between motor RSNs and gross motor skills (p=0.012; r=0.754) were observed in TSC infants without autism, but not in TSC infants with autism, which could suggest altered motor processing. There were no significant differences in RSNs according to seizure history. CONCLUSIONS: Negative correlation between auditory RSN as well as positive correlation between motor RSN and developmental outcome measures might reflect different brain mechanisms and, when identified, may be helpful in predicting later function. A larger study of TSC patients with a healthy control group is needed before auditory and motor RSNs could be considered as neurodevelopmental outcome biomarkers.